The relationship between knowledge and adherence to insulin therapy in type 2 diabetes mellitus patients at the outpatient clinic of Budi Kemuliaan Hospital, Batam City - Rachmayanti, Aprilya Sri; Hasan, Nahrul; Sammulia, Suci Fitriani; Haryani, Reny; Suhaera, Suhaera; Meilanda, Rastria; Sinaga, Asmina (Science Midwifery, 2023)
Diabetes mellitus is a prevalent degenerative disease in today's society. Indonesia, as one of the countries with the largest population, has experienced a significant increase in the global prevalence of type 2 diabetes mellitus. Approximately 20% of the Indonesian population uses insulin with or without oral antidiabetic drugs. It has been found that patient compliance in Indonesia does not meet the recommended glycemic targets. This non-compliance is attributed to patients' lack of knowledge and understanding about insulin and its use in therapy. This study aims to explore the relationship between knowledge and adherence to insulin therapy among type 2 diabetes mellitus patients in the outpatient clinic of Budi Kemuliaan Hospital, Batam City. A descriptive correlation method was employed, utilizing a prospective cross-sectional research design. The sample was selected using purposive sampling, resulting in a total of 60 patients who met the inclusion criteria. Data were collected through two questionnaires: a knowledge questionnaire and the Medication Adherence Scale (MMAS). Statistical analysis included frequency distribution tests and chi-square tests. The research findings revealed a significant relationship between knowledge and adherence to insulin therapy, with a Chi-Square test yielding a P-Value of 0.029, where P-Value α < 0.05. In conclusion, this study demonstrates a significant correlation between knowledge and adherence to insulin therapy among type 2 diabetes mellitus patients. It is recommended that healthcare providers at Budi Kemuliaan Hospital deliver accurate information to patients to enhance their knowledge and understanding of insulin use, as well as the potential complications associated with diabetes mellitus.